2020
DOI: 10.20473/ijtid.v8i1.10721
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Severe Dengue Infections in Children

Abstract: The  incidence of dengue fever increase annually and can increase morbidity and mortality. Dengue fever is mosquito-borne disease and caused by one of four serotype dengue viruses. Severe dengue is characterized either by plasma leakage, fluid accumulation, respiratory distress, severe bleeding, or organ impairment. Mortality and serious morbidity of dengue were caused by several factors including the late recognition of the disease and the changing of clinical signs and symptoms. Understanding the prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…After including two studies in the metaanalysis, we obtained an OR of 1.02 (95%CI 0.60 to 1.75) with no heterogeneity (I2=0%). 33,48 In terms of clinical manifestations, we found that neurologic signs were strongly associated with the progression of severe dengue. Neurological manifestations may include drowsiness, convulsions, decreased consciousness, or lethargy.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…After including two studies in the metaanalysis, we obtained an OR of 1.02 (95%CI 0.60 to 1.75) with no heterogeneity (I2=0%). 33,48 In terms of clinical manifestations, we found that neurologic signs were strongly associated with the progression of severe dengue. Neurological manifestations may include drowsiness, convulsions, decreased consciousness, or lethargy.…”
Section: Resultsmentioning
confidence: 86%
“…Three studies reported an association between nutritional status and progression to severe dengue. 33,48,59 Baiduri et al 33 showed a strong relationship between overweight-obesity and progression to severe dengue with an RR of 94 (95%CI 4.47 to 1989) through a multivariate analysis approach. Tantracheewathorn et al 48 and Dewi et al 59 found no association between normal nutritional status and progression to severe dengue.…”
Section: Resultsmentioning
confidence: 99%
“…No statistical significance occurred because all research subjects showed PT prolongation >6 s so it was not possible to know the PT value that played a role as predictor factor in mortality. However, PT played a role in patient survival in the first 6 h, which was 94.1% of patients were still alive and decreased to 82.4% at 24 h. This shows that PT prolongation is closely related to the presence of an unresolved shock process [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A rapid decrease in thrombocyte count is associated with the severity of dengue virus infection as observed in this study, in which 93.8% of patients with a thrombocyte count 50,000/L in the first 6 h after DSS diagnosis were still alive but decreased to 81.3% after 24 h of treatment. This is closely related to bleeding manifestations, such as gastrointestinal bleeding that occurs in 58.8% of patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%